Scenario Analysis on Energy Transition & Energy Security: A Case Study on Madhesh Province of Nepal - Sapkota, Ganesh; Shakya, Shree Raj (Journal of Advanced College of Engineering and Management, 2024)
The paper has taken Madesh province as the area of study and it presents the study of energy demand emission analysis along with the energy security state of the province. The government's Net-zero targets had been taken into account to create the scenarios where the overview of the province-level energy security indicators is calculated in the time frame taking 2019 as the base year and 2050 as the final year of analysis. The energy demand and emission of different sectors of Madhesh province are compared and the scenario and their impact on the energy security indicators are compared. The elasticity of the different sectors based on GDP is used to determine the baseline scenario of the study which is then compared with the government scenario to observe fuel savings and reduction of import of fuel can be seen. Thus, the study shows energy consumption can be reduced by 35.92% which results in an emission reduction of 87.01% in the year 2050. The energy intensity can be improved up to 36% compared to the no-intervention scenario if the policies are implemented and electricity consumption capacity will triple in the year 2050 compared to the baseline.